Impelementasi Pembelajaran Pendidikan Agama Kristen di Abad 21 - Daniel S. Tjandra (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
The era of globalization is inevitable, willing or unwilling to be ready or not ready for everyone to face globalization. The era of globalization can be said as an era of openness, an era of technology that is close to people's lives and even inherent in everyday life. Globalization colors and influences all aspects of life without exception the realm of education experiences or is affected by the effects of the times, globalization and technological sophistication. Education makes it possible to use all the advances of the times to produce an educational goal that shapes the complete human to face his day. 21st century learning provides a prominent change in the world of education, where learning is no longer focused on the results achieved, but on the learning process itself. Forming the competencies of students who have high-level thinking skills, are creative, communicative, and collaborative. This discussion will provide an understanding of 21st century learning implemented in Christian Religious Education subjects. Christian religious learning is expected to follow the development of 21st century learning so that in conveying learning content can prepare students to welcome the 21st century. Thus the curriculum in Indonesia is developed, and the 2013 curriculum is used now as part of responding to the challenges of the 21st century. Abstrak Era globalisasi tidak dapat dihindari, mau atau tidak mau siap atau tidak siap setiap orang menghadapi globalisasi. Era globalisasi dapat dikatakan sebagai era keterbukaan, era teknologi yang dekat dengan kehidupan masyarakat bahkan melekat dalam kehidupan sehari-hari. Globalisasi mewarnai dan mempengaruhi segala aspek kehidupan tanpa terkecuali ranah pendidikan mengalami atau tekena efek dari kemajuan zaman, globalisasi dan kecanggihan teknologi. Pendidikan memungkinkan meng-gunakan segala kemajuan zaman untuk menghasilkan sebuah tujuan pendidikan yang membentuk manusia secara lengkap untuk menghadapi zamannya. Pembelajaran abad 21 memberikan sebuah perubahan yang menonjol dalam dunia pendidikan, dimana pembelajaran bukan lagi dipusatkan kepada hasil yang dicapai, namun kepada proses pembelajaran itu sendiri. Membentuk kompetensi peserta didik yang memiliki keterampilan berpikir tingkat tinggi, kreatif, komunikatif, dan kolaborasi. Pada pembahasan kali ini akan memberikan pemahaman tentang pembelajaran abad 21 yang diimplementasikan dalam mata pelajaran Pendidikan Agama Kristen. Pembelajaran Agama Kristen diharapkan mengikuti perkembangan pembelajaran abad 21 sehingga dalam menyampaikan konten pembelajaran dapat mempersiapkan peserta didik menyongsong abad 21. Dengan demikian Kurikulum di Indonesia dikembangkan, dan Kurikulum 2013 yang digunakan sekarang sebagai bagian dalam menjawab tantangan zaman abad 21.